Hubungan Status Gizi dengan Kejadian Menarche pada Siswi Sekolah Dasar - Hasna Rizki Puspaningrum; Dwi Sri Handayani; Diah Nur Anisa (Infomasi dan Promosi Kesehatan, 2024)
The average age of menarche incidence in Indonesia in 2018 was 13 years old at 55.12%. Meanwhile, in the province of Yogyakarta, the average is 12.45 years. Generally, menarche occurs at the age of 12 years, but currently there is a tendency for menarche at a younger age. Menarche is influenced by several factors, one of which is nutritional status. These events are at risk of eating disorders, premature sex, obesity, early menopause, diabetes and breast cancer. The purpose of this study is to determine the relationship between nutritional status and the incidence of menarche. The research design used correlation analysis with a crossectional approach and a sample of 46 students was taken with a total sampling through inclusion and exclusion criteria.The students taken as samples were students who had experienced menarche. Data were measured using BMI measurements and menarche incidence questionnaires. Data analysis uses spearman rank. The results of nutritional status (p-value = 0.0592) had a p-value of >0.05, indicating that there was no relationship between nutritional status and the incidence of menarche. The result of the correlation coefficient of -0.081 is in the range of 95% C.I value with lower – upper of (-0.373) – 0.221. This means that there is no relationship between nutritional status and the incidence of menarche with a very weak negative direction. It is hoped that adolescent girls can regulate a healthy lifestyle by reducing junk food to avoid the risk of menarche at an abnormal age. kEYWORD: Nutritional, Menarche, Elementary School Student